Preparation of Methylammonium Tin Iodide (CH3NH3SnI3) Perovskite Thin Films via Flash Evaporation. Issue 18 (17th July 2019) - Mortan, Claudiu; Hellmann, Tim; Clemens, Oliver; Mayer, Thomas; Jaegermann, Wolfram
Abstract : Using the one‐step flash evaporation technique, it is possible to deposit a film of methylammonium tin iodide (MASI, CH3 NH3 SnI3 ) from the solid perovskite powder that is prepared by a mechanochemical synthesis, without the use of any solvents. The source material and the film are characterized by X‐ray photoelectron spectroscopy (XPS) and X‐ray diffraction (XRD). The XPS measurements show that the MASI film is stoichiometric and is a p‐type material with the Fermi level of 0.4 eV above the valence band maximum (VBM) and a bandgap of 1.3 eV. The XRD pattern of the film reveals the formation of MASI perovskite of high purity, crystallizing with pseudo‐cubic symmetry, having the lattice parameters a  ≈  c  = 6.239(8) Å. Abstract : Using the one‐step flash evaporation technique, it is possible to deposit a film of methylammonium tin iodide (MASI, CH3 NH3 SnI3 ) from the solid perovskite powder that is prepared by a mechanochemical synthesis, without the use of any solvents.